A critical evaluation of “leakage” at the cochlear blood-stria-barrier and its functional significance - Ohlemiller, Kevin K.; Dwyer, Noël; Henson, Veronica; Fasman, Kaela; Hirose, Keiko (Frontiers in Molecular Neuroscience, 2024)
The blood-labyrinth-barrier (BLB) is a semipermeable boundary between the vasculature and three separate fluid spaces of the inner ear, the perilymph, the endolymph and the intrastrial space. An important component of the BLB is the blood-stria-barrier, which shepherds the passage of ions and metabolites from strial capillaries into the intrastrial space. Some investigators have reported increased ‘leakage’ from these capillaries following certain experimental interventions, or in the presence of inflammation or genetic variants. This leakage is generally thought to be harmful to cochlear function, principally by lowering the endocochlear potential (EP). Here, we examine evidence for this dogma. We find that strial capillaries are not exclusive, and that the asserted detrimental influence of strial capillary leakage is often confounded by hair cell damage or intrinsic dysfunction of the stria. The vast majority of previous reports speculate about the influence of strial vascular barrier function on the EP without directly measuring the EP. We argue that strial capillary leakage is common across conditions and species, and does not significantly impact the EP or hearing thresholds, either on evidentiary or theoretical grounds. Instead, strial capillary endothelial cells and pericytes are dynamic and allow permeability of varying degrees in response to specific conditions. We present observations from mice and demonstrate that the mechanisms of strial capillary transport are heterogeneous and inconsistent among inbred strains.